Erratum to: Averaging Generalized Scalar Field Cosmologies I: Locally Rotationally Symmetric Bianchi Iii and Open Friedmann–Lemaître–Robertson–Walker Models (the European Physical Journal C, 2021 81 5 414 10.1140/Epjc/S10052-021-09185-7) - Gonzalez-Banda, E (Springer Science and Business Media Deutschland GmbH, 2021)
In this article the following acknowledgment was replaced: This research was funded by Agencia Nacional de Investigación y Desarrollo-ANID through the program FONDECYT Iniciación grant no. 11180126 and by Vicerrectoría de Investigación y Desarrollo Tecnológico at Universidad Católica del Norte. Ellen de los Milagros Fernández Flores is acknowledged for proofreading this manuscript and improving the English. We thank anonymous referee for his/her comments which have helped us improve our work. The correct acknowledgment reads as follows: The research of Genly Leon and Esteban González was funded by Agencia Nacional de Investigación y Desarrollo- ANID through the program FONDECYT Iniciación grant no. 11180126. Alfredo D. Millano was supported by Agencia Nacional de Investigación y Desarrollo - ANID - Subdirección de Capital Humano/Doctorado Nacional/año 2020- folio 21200837. Claudio Michea was supported by Agencia Nacional de Investigación y Desarrollo - ANID - Subdirección de CapitalHumano/Doctorado Nacional/año 2021- folio The original article can be found online at https://doi.org/10.1140/ epjc/s10052-021-09185-7. a e-mail: genly.leon@ucn.cl (corresponding author) b e-mail: esteban.gonzalezb@usach.cl c e-mail: samuel.lepe@pucv.cl d e-mail: claudio.ramirez@ce.ucn.cl e e-mail: alfredo.millano@alumnos.ucn.cl 21211604. Vicerrectoría de Investigación y Desarrollo Tecnológico at Universidad Católica del Norte is anknowleged by finacial support. Ellen de los Milagros Fernández Flores is acknowledged for proofreading this manuscript and improving the English. We thank anonymous referee for his/her comments which have helped us improve our work. The original article has been corrected. © The Author(s) 2021.